Gluing, catching and connecting: how informal childcare strengthens single mothers' employment trajectories. (October 2016) - Brady, Michelle
Research on single mothers' employment overwhelmingly focuses on the importance of access to formal childcare at a single point in time . However, to understand the relationship between childcare and single mothers' employment we must consider their access to and use of multiple forms of childcare – their childcare packages – and how these change over time. Drawing on a longitudinal qualitative study and employing the concepts of 'caringscapes' and 'work-time/childcare-time', this article highlights how childcare packages shape single mothers' employment trajectories. Informal carers play a crucial role within mixed (formal and informal) childcare packages in helping mothers bring children's needs, work-time and childcare-time into alignment, thus strengthening their employment trajectories. Informal carers achieve this effect by: (1) increasing the total hours of non-parental care; (2) 'gluing' together complex jigsaws of care; (3) offering a 'safety net' in times of crisis; and (4) playing a 'connector' role during employment transitions.